ICASSP 2020 - 2020 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2020
DOI: 10.1109/icassp40776.2020.9053497
|View full text |Cite
|
Sign up to set email alerts
|

Using Panoramic Videos for Multi-Person Localization and Tracking In A 3D Panoramic Coordinate

Abstract: This work proposes a new human-related video processing task named 3D panoramic multi-person localization and tracking. With a benchmark dataset and a simple yet effective solution, it establishes a new paradigm for multi-person tracking systems and related applications. Unlike existing methods that can only work on a 2D coordinate or a narrowangle-view 3D coordinate, our proposal can maximally explore the 3D trajectory information of tracking targets. This is approached by applying camera geometry to transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The evaluation was performed offline on the pre-recorded test set with a PC equipped with an NVIDIA GTX 1650 GPU, 16 GB of RAM, and an Intel i7-4790 CPU. We also compared the performance of our proposal with the Multi-person Panoramic Localization and Tracking (MPLT) [26] introduced in Sec. 2.2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation was performed offline on the pre-recorded test set with a PC equipped with an NVIDIA GTX 1650 GPU, 16 GB of RAM, and an Intel i7-4790 CPU. We also compared the performance of our proposal with the Multi-person Panoramic Localization and Tracking (MPLT) [26] introduced in Sec. 2.2.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies used a couple of calibrated omnidirectional cameras to achieve accurate 3D people tracking in panoramic videos [25]. The proposal of Yang et al [26], called Multi-person Panoramic Localization and Tracking (MPLT), instead relies on four calibrated perspective cameras, positioned such that they cover a field of view of 360 • to simulate an omnidirectional camera. The OpenPifPaf framework [13] is used for skeleton detection and a pinhole camera model is used to map detections in the 3D space, under the assumption that the height of a person is almost constant.…”
Section: People Trackingmentioning
confidence: 99%
“…In Yang et al [16], a multi-person panoramic localization and tracking (MPLT) dataset is presented to enable model evaluation for 3D panoramic multi-person localization and tracking. It represents real-world scenarios and contains a crowd of people in each frame.…”
Section: • Videos Datasetsmentioning
confidence: 99%
“…Some researchers showed that by using post-processing, 360-degree video streaming can support functions other than only streaming videos. Rhee showed that 3D virtual objects can be seamlessly composited on 360-degree streaming videos [13], and Yang et al [32] presented 360-degree videos that can generate person localization data by proposing a multi-person localization and tracking algorithm for 360-degree videos. We adopted the 360 technique from the aforementioned studies because it can support a sophisticated monitoring function from a micro-perspective.…”
Section: Micro Perspective Of Udt Using 360 Techniquesmentioning
confidence: 99%